Job, Boethius, and Epic Truth - Astell, Ann W. (Book collections on Project MUSE., 2019)
Calling into question the common assumption that the Middle Ages produced no secondary epics, Ann W. Astell here revises a key chapter in literary history. She examines the connections between the Book of Job and Boethius' s Consolation of Philosophy ...